Design of Temperature Control Instrument in Drying Process of Vanilla (Vanilla planifolia Andrews) - Wibisono, Yusuf; Djojowasito, Gunomo (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
The quality of dried vanilla depends largely on the temperature control during drying. Vanilla is traditionally solar dried, thus the product quality is unpredictable and is extremely influenced by weather. In order to obtain a good quality product, the moisture content of the vanilla must be reduced gradually to a level of about 25-30%, hence the control of temperature during drying is very important. The study was aimed to design a temperature control instrument in such a process using a negative temperature coefficient (NTC) sensor, with an automatic on-off mechanism on a preset temperature level. The results showed that at a preset temperature of 50Â°, the automatic on mechanism of the instrument responded well when the temperature decreased to a level of 1-5oC from the preset temperature. Â Key words: temperature control, drying, NTC sensor, vanilla